The Ecological Footprint Nowadays - Daferera, Maria; Abaskharoun, Mariam; Theodoratou, Evangelia (Open Schools Journal for Open Science, 2019)
This assessment refers to the ecological footprint which is a way to measure the impacts of human activities on Earth. It basically calculates the demand and consumption that measures the needs of a society, as well as the waste and greenhouse gases that generates daily in productive sea and fertile land areas. Moreover, it measures all the natural resources needed to support the material needs of a population or person through the technology, lifestyle and habits of each country. Subsequently we are going to examine the advantages and disadvantages of the phenomenon that human activities provoke and the ways to eliminate the caused problem. The world-average ecological footprint in 2013 was 2.8 global hectares per person and the average per country ranges from over 10 to under 1 global hectares per person. There is also a high variation within countries, based on individual lifestyle and economic possibilities that we also examine. Summarizing all those effects we are going to analyze open international data as far as the metabolism of the ecological footprint concerns in our word but especially in our country to form prospects for our planet the principles of life cycle assessments with the aid of statistics and charts.